2020
DOI: 10.1007/s40519-020-01025-z
|View full text |Cite
|
Sign up to set email alerts
|

The Polish version of the Düsseldorf Orthorexia Scale (PL-DOS) and its comparison with the English version of the DOS (E-DOS)

Abstract: Purpose Although orthorexia nervosa, the fixation on health-conscious eating behaviour, was first described in the 90 s, there is no clear understanding whether existing ON measures are appropriate for its assessment. The objectives of the present study were to: (1) examine the psychometric properties of the Polish version of the DOS (PL-DOS) and to compare the PL-DOS with the English version of the DOS (E-DOS) as well as (2) evaluate the prevalence of ON among Polish university students and compare the preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
3
18
1
Order By: Relevance
“…A previous study [ 49 ] has shown that eating-related variables (pathological eating, eating pattern, and MD), compulsive symptoms, and subjective social status were predictors of ON in adults. It is possible that university students who adopt a Mediterranean eating pattern are more likely to pay attention to healthy eating and are more concerned about food, avoiding all foodstuffs subjectively considered to be “unhealthy” [ 50 ]. This is a topic worthy of further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [ 49 ] has shown that eating-related variables (pathological eating, eating pattern, and MD), compulsive symptoms, and subjective social status were predictors of ON in adults. It is possible that university students who adopt a Mediterranean eating pattern are more likely to pay attention to healthy eating and are more concerned about food, avoiding all foodstuffs subjectively considered to be “unhealthy” [ 50 ]. This is a topic worthy of further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…In the current sample, Cronbach's alpha coefficient of the DOS was 0.84. In the present study, we used the Polish version of this questionnaire (PL-DOS) [37].…”
Section: The Düsseldorf Orthorexia Scale (Dos)mentioning
confidence: 99%
“…The DOS shows good internal consistency (Cronbach’s alpha = 0.84) and good retest reliability ( r = 0.67 to 0.79, p = 0.001 between three reference dates) [ 39 ]. In the present study, the Polish version (PL-DOS) [ 15 ] and the Lebanese version of the DOS [ 41 ] were used (Cronbach’s α Poland = 0.834 and Cronbach’s α Lebanon = 0.896).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous researchers have reported the prevalence of ON, with values varying considerably according to the measure used to evaluate the same construct (e.g., ORTO-15 test, the Düsseldorf Orthorexia Scale), the selected population (e.g., clinical versus non-clinical samples), and the nationality [ 13 ]. The prevalence of ON ranges from 1% in the general U.S. population [ 14 ] to much higher percentages, particularly among university students worldwide, e.g., 6.6% in a sample of Polish students [ 15 ], 8% in a sample of U.S. students [ 16 ], and 10.5% in a sample of Spanish students [ 13 ]. It has been suggested that the vast inconsistency was mainly due to the difference of instruments used, but not due to cultural differences [ 14 ].…”
Section: Introductionmentioning
confidence: 99%